Real-time dynamic loading and thermal diagnostic of power transformers. - Lachman, M.F (IEEE Transactions on power delivery)
A comprehensive approach to dynamic loading of power transformers is presented. It is based on the Annex G equations in the latest IEEE Loading Guide. The IEEE work is enhanced through a continuous update of rated temperatures. The algorithm was evaluated with nine transformer-months of real-time field data. Field observations and comparison with the IEEE Clause 7 and IEC thermal models are presented. Dynamic loading ratings are determined considering limitations imposed by top-oil and hottest-spot temperatures, load current and loss-of-life as defined by the IEEE for various types of loading. The rating calculations also consider temperatures of bushings, voltage, present value and historical trend of ambient temperature, preload parameters, cooling mode during the overload, moisture content in the paper, presence of bushing enclosures, and the type of oil-preservation system.